Effects of Pantawid Pamilyang Pilipino Program (4P’s) in the Province of Sultan Kudarat - Roque, Jonathan (Journal of Interdisciplinary Perspectives, 2025)
This study examines the effects of the Pantawid Pamilyang Pilipino Program (4Ps) on poverty alleviation, health, and education in Sultan Kudarat Province. The research addresses the gap in understanding the program's impact on beneficiaries, focusing on its effectiveness in improving living conditions. Utilizing a descriptive research design, data were collected from 617 randomly selected beneficiaries across 11 barangays through a survey questionnaire. The analysis revealed that while implementing cash grants was perceived as moderately effective, the health benefits provided through PhilHealth were viewed positively. The findings indicate significant improvements in poverty alleviation, maternal health, and educational outcomes, with mean scores reflecting a highly effective impact. The study concludes that the 4Ps program is essential for sustainable development and enhancing the quality of life for families in Sultan Kudarat. Continued efforts are necessary to address implementation challenges, such as delays in cash grant disbursement, to maximize the program's overall effectiveness.